Combining ability analysis of maize lines under optimal and low nitrogen stress. Issue 1 (November 2021) - Andayani, Nining N.; Arif Subchan, M.; Efendi, Roy; Aqil, M.; Azrai, M.
Abstract: Most of the land for maize development in Indonesia has low N limiting factor, thus it is necessary to develop a proper maize breeding programs tolerant to low N conditions. One of the breeding methods suitable for low N evaluation is the diallel method between inbred parents (homozygous lines) that are tolerant of low N stress. The aim of this study was to assess the genotype tolerance to low N with comparable yields. The research consisted of two stages. The first stage is the development of hybrid maize grains (F1) using the half diallel cross method. This activity was carried out in KP. Maros, Research Center for Cereal Crops. A half-diallel cross refers to the Griffing IV method, by involving 11 low N-tolerant genotypes (AVLN 100-1, AVLN 118-2, AVLN 122-2, AVLN 124-4, AVLN 32-3, AVLN 83-1, AVLN 83-4, AVLN 83-6, AVLN 86-2, MAL 04, and AVLN 124-9). The second stage was carried out in KP. Bajeng to evaluate 52 genotypes of hybrid maize from diallel crosses plus four hybrid varieties Advanta 777, Bisi 18, P 27 and JH 37 for control. The experiment was carried out under conditions of low N stress (100 kg N/ha) and normal N (200 kg N/ha). The experiment used a randomized block design with three replications. Hybrids that are tolerant (T) under conditions of low N stress was best indicated by AVLN 83-4/AVLN 124-4 genotype pair, with significant higher grain yield than Bisi-18 and JH 37 varieties. This hybrid produced average grain yield of 7.87 t/ha under both conditions. Inbred maize genotypes classified as medium tolerant (MT) were AVLN 83-4/AVLN 124-9, AVLN 124-4/AVLN 86-2, AVLN 122-2/AVLN 124-4, AVLN 83-1/AVLN 124-9, has similar yield potential as to the control varieties.